Eudesmane-type and agarospirane-type sesquiterpenes from agarwood of Aquilaria agallocha. (December 2021) - Xie, Yanqiao; Song, Leixin; Li, Chunge; Yang, Yingbo; Zhang, Siyu; Xu, Hong; Wang, Zhengtao; Han, Zhuzhen; Yang, Li
Abstract: Eleven previously unreported sesquiterpenes, including nine eudesmane-type (agalleudesmanol A-I) and two agarospirane-type sesquiterpenes (agarospiranic aldehyde A-B), together with eight known sesquiterpenes, were isolated from the agarwood of Aquilaria agallocha Roxb. The structures were established based on extensive spectroscopic analyses, including infrared (IR), high-resolution electrospray ionisation mass spectrometry (HRESIMS), nuclear magnetic resonance (NMR), X-ray diffraction, quantum chemical calculations based on empirical electronic circular dichroism (ECD) data, and DP4+ probability analysis. The bioactivity of these undescribed compounds against lipopolysaccharide (LPS)-induced NO production in RAW 264.7 cells was evaluated. Compounds 1 and 2 exhibited significant anti-inflammatory activities, with IC 50 values of 5.46–14.07  μ M (aminoguanidine as positive control, IC 50 20.33 ± 1.08  μ M). Graphical abstract: Image 1 Highlights: Eleven undescribed sesquiterpenes were isolated from Aquilaria agallocha Roxb . Their structures were elucidated by extensive spectroscopic analyses. The absolute configurations were defined by X-ray crystallography and ECD calculation. Two compounds showed significant anti-inflammatory activities.